MODEL RPP BAHASA INGGRIS BERBASIS BELAJAR MANDIRI - Imroatus Solikhah (Universitas Islam Balitar, 2017)
This study examines instructional objectives, teaching materials, and teaching strategies in English lesson plan. The study uses evaluation design implementing content analysis. An English lesson plan obtained from online data is analyzed. The study reveals that the lesson plan does not formulate appropriately components of instructional objectives and its indicators. The use of action verbs in Bloom taxonomy of instruction is not well identified in the indicators and instructional objectives. Sequence of instructional objective shows that instruction analysis is not applied. As a result, teaching materials are not well designed to show topics as the main teaching materials. Indication of how teacher develops a teaching material that links to instructional objectives, teaching strategies, and evaluation is absent. The lesson plan needs modification in all levels of instructional design more considerably.